Respuesta :

Answer:

u = 3w-4.5

Step-by-step explanation:

w being the independent variable assumes that u will become the dependent variable. Therefore the equation needs to turn into u = aw + b

-2u + 6w = 9

*subtract 6w from both sides

-2u = 9-6w

*divide both sides by -2

u = -4.5+3w

*rearrange to make it look nicer

u = 3w-4.5

therefore: the w value doesn't care what the u value is making it independent but the u value will change from the w value making it dependent

Answer:

u = 3w - 4.5

Step-by-step explanation:

Look at attachment:

Hope this helps!

Ver imagen ninjathan300
ACCESS MORE